Detoxification of Dissolved SO(2) (Bisulfite) by Terricolous Mosses - BHARALI, BHAGAWAN (Oxford University Press, 2006)
• Background and Aims The widespread calcifuge moss Pleurozium schreberi is moderately tolerant of SO(2), whereas Rhytidiadelphus triquetrus is limited to calcareous soils in regions of the UK that were strongly affected by SO(2) pollution in the 20th century. The proposition that tolerance of SO(2) by these terricolous mosses depends on metabolic detoxification of dissolved bisulfite was investigated. • Methods The capacities of the two mosses to accelerate loss of bisulfite from aqueous solutions of NaHSO(3) were studied using DTNB [5, 5-dithio-(2-nitrobenzoic acid)] to assay bisulfite, and HPLC to assay sulfate in the incubation solutions. Incubations were performed for different durations, in the presence and absence of light, at a range of solution pH values, in the presence of metabolic inhibitors and with altered moss apoplastic Ca(2+) and Fe(3+) levels. • Key Results Bisulfite disappearance was markedly stimulated in the light and twice as great for R. triquetrus as for P. schreberi. DCMU, an inhibitor of photosynthetic electron chain transport, significantly reduced bisufite loss. • Conclusions Bisulfite (SO(2)) tolerance in these terricolous mosses involves extracellular oxidation using metabolic (photo-oxidative) energy, passive oxidation by adsorbed Fe(3+) (only available to the calcifuge) and probably also internal metabolic detoxification.